Hubungan Antara Kepuasan Kerja Dengan Motivasi Kerja Pada Pegawai Balai Kota Surakarta - Sukarno, Emirda Tri Via; , Achmad Dwityanto, S.Psi, M.Si (2017)
The purpose of this research is to know the relation between job satisfaction with employee motivation to work on the Town Hall of Surakarta. The hypothesis proposed that there are positive relationship between the job satisfaction with employee motivation to work on the Town Hall of Surakarta. The subject in this study was an employee at the BPPKAD (Revenue Agency Financial and assets Management Area) the Town Hall of Surakarta as many as 90 people. The sampling techniques used in this research was using a technique purposive sampling. This research used quantitative methods with work motivation and job satisfaction scale. Data analysis on this research using SPSS program version 20.00 with product moment correlation method, obtained 0.721 with significance p = 0.000; (p 0.01 ˂) this indicates that there is a very significant positive relationships between the variables job satisfaction with work motivation. Effective contribution from two variables showed value (r2) = 0.519 it means variable job satisfaction affects 51,9% to work motivation and there is 48,1% is influenced by other factors. Job satisfaction relatively high with with the empirical mean of the mean 82.39 and hypothetical amounted to 67.5. work motivation relatively high with empirical mean of the mean 91.16 and hypothetical of 72.5